Intellectual stimulation and team creative climate in a professional service firm. Issue 1 (3rd April 2018) - Sandvik, Alexander Madsen; Croucher, Richard; Espedal, Bjarne; Selart, Marcus
Abstract : Purpose: The purpose of this paper is to investigate the precise role of intrinsic motivation and autonomy in relation to intellectual stimulation in creating a creative climate in a professional services firm. The intention is to discover whether theories that stress the primacy of the need for intrinsic motivation and autonomy over other managerial goals such as monitoring find support. Design/methodology/approach: The authors propose and test a model for the relationship of interest. The theoretical model is tested through analysis of multilevel data gathered across in two iterations over two years from 177 employees and 64 teams in one company. Findings: The authors find that intrinsic motivation and autonomy mediate the relationship between intellectual stimulation and creative climate. Autonomy exercises a stronger mediating effect than intrinsic motivation. Research limitations/implications: The single company research context's specificity; causal relationships between variables cannot be empirically investigated; the verified research model cannot claim to represent how the organization actually functions, for which qualitative work is required. Practical implications: Theories stressing the primacy of employee autonomy are supported over those stressing a need for management to monitor and control autonomy-seeking employees. Originality/value: This paper shows the vital mediating role of employee autonomy and to a lesser extent intrinsic motivation in a professional service firm context.